Implementasi Sistem Pelayanan Administrasi Kependudukan Desa di Kantor Desa Karya Makmur - Firra Katria, Almabilla; Fujianti, Linda; Yang, Yang Agita Rindri (Manutech : Jurnal Teknologi Manufaktur, 2024)
Currently, technological developments continue to develop rapidly so that more and more digitalization is used by people around the world to carry out activities in various aspects, one of which is village digitalization which is used for community service activities. The village used as the research object is Karya Makmur village which is located in Pemali District, Bangka Regency, Bangka Belitung Islands Province. Karya Makmur Village faces challenges in aligning population administration processes with developments in information technology. Implementation of a population administration service system that is integrated with online mail services, payment of village fees using QR-Code, and deadline reminders via WhatsApp Gateway are strategic solutions to improve service quality. In contrast to previous research which still focused on manual systems, this research offers an innovative digital approach to simplify the administrative service process at the village level. The method applied involves direct observation, interviews and literature studies to understand the population administration service system. The Prototyping Method is a method used as a systematic development method. The results of the evaluation of the population administration service system using the User Acceptance Testing (UAT) method show that this system can be considered feasible and effective for use with a success percentage reaching 95.38 percent. Thus, this population administration system makes the process of providing services to the community in Karya Makmur village more efficient.